PEMETAAN PERUBAHAN PEMANFAATAN LAHAN MANGROVE MENJADI LAHAN BUDIDAYA TAMBAK STUDI KASUS TAMBAK DESA SEBAMBAN BARU KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Fatmawati Fatmawati; Baharuddin Baharuddin (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2012)
The purpose of this study was to determine the change in mangrove use to aquaculture. The research was conducted in the village of Sebamban Baru, Sungai Loban District, Tanah Bumbu Regency of South Kalimantan Province. processing of Landsat ETM imagery for mapping mangrove and ponds land use change from 2001and 2010 using ER Mapper software version 7.0.The results showed that the change of mangrove land in the village of Sebamban Baru from 2001 to 2010. 2001 based on the interpretation of the image of vast mangrove 482,321 ha and 254,731 ha of ponds wide, whereas in 2010 there isa change widespread utilization of mangroves into fishponds 346,814 ha and368,542 ha. cause land area of 135 507 ha of mangrove decline and an increase inponds 135,507 hectares wide. From the ecological aspect is emphasized that the formation of spatial coastal areas in Tanah Bumbu district must consider the mangrove forests, and keep doing aquaculture activities and still maintain mangrove conservation by setting the ratio of mangrove land available if the location was built fishpond.